2018
DOI: 10.3389/fnins.2018.00054
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological and Behavioral Differences between Older and Younger Adults When Processing Violations of Tonal Structure in Music

Abstract: Aging is associated with decline in both cognitive and auditory abilities. However, evidence suggests that music perception is relatively spared, despite relying on auditory and cognitive abilities that tend to decline with age. It is therefore likely that older adults engage compensatory mechanisms which should be evident in the underlying functional neurophysiology related to processing music. In other words, the perception of musical structure would be similar or enhanced in older compared to younger adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 69 publications
1
15
0
1
Order By: Relevance
“…This means we can predict it with high precision (i.e., with high confidence), given the preceding context of a scale. Later in the movement (after the beginning of the development section), the same passage is modified in a way that the last note of the scale is out of key -and is therefore irregular or improbable given the preceding syntactic context (see also Figure 2 [45][46][47][48][49][50][51][52][53][54]. In contrast to the classical MMN [28][29][30] -that depends on regularities in ongoing auditory input -the ERAN depends on syntactic knowledge that transcends current auditory sensations.…”
Section: Predictive Processes In the Perception Of Harmonymentioning
confidence: 99%
“…This means we can predict it with high precision (i.e., with high confidence), given the preceding context of a scale. Later in the movement (after the beginning of the development section), the same passage is modified in a way that the last note of the scale is out of key -and is therefore irregular or improbable given the preceding syntactic context (see also Figure 2 [45][46][47][48][49][50][51][52][53][54]. In contrast to the classical MMN [28][29][30] -that depends on regularities in ongoing auditory input -the ERAN depends on syntactic knowledge that transcends current auditory sensations.…”
Section: Predictive Processes In the Perception Of Harmonymentioning
confidence: 99%
“…Out-of-Tune notes are more salient than Out-of-Key notes because they violate the general chromatic scale used in all Western music, and not a diatonic scale that is specific to a melody or song. Supporting this hypothesis, previous work has shown that the ability to detect Out-of-tune notes was associated with the ERAN and not the P600, and that performance on a click-detection task was reduced when the click followed an Out-of-Tune note, but not an Outof-Key or In-Key note (Lagrois et al, 2018). Although we did not replicate the previously reported relationship between ERAN and Accuracy; Accuracy was lower in Nmus compared to STmus, but the P600 responses in these groups was comparable.…”
Section: Group Differences On P600mentioning
confidence: 79%
“…A set of 40 melodies were used as stimuli for the melody task. This is the same set of melodies that was first used by Brattico et al (2006), have since been used in a variety of music perception studies (e.g., Peretz et al, 2009;Zendel et al, 2015a;Lagrois et al, 2018;Vuvan et al, 2018). All melodies were in a major key and varied in rhythm.…”
Section: Active Melody Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the little evidence we have investigating music perception in older adults suggests that it is generally preserved (Halpern, Bartlett, & Dowling, 1995Halpern, Kwak, Bartlett, & Dowling, 1996;Halpern et al, 2017). In some cases the performance of a musical task is preserved, but the underlying brain activity changes, suggesting that older adults may automatically compensate for declining cognitive or perceptual abilities in the musical domain (Halpern et al, 2017;Lagrois, Peretz, & Zendel, 2018). This may be due to the development of compensatory mechanisms similar to those found for speech in noise perception, where older adults use contextual information to help overcome age-related changes in hearing and cognitive abilities (Birren & Fisher, 1995;Horn, 1982;Horn & Cattell, 1967;Madden, 1992;Pichora-Fuller, Schneider, & Daneman, 1995).…”
Section: Introductionmentioning
confidence: 99%